Birthweight After Frozen Embryos Formed on the Fifth Day Versus the Sixth Day: A Retrospective Analysis Including 17,127 Singleton Newborns - Yang, Junlan; Wang, Ze; Cao, Hairu; Liu, Lu; Yuan, Qiaona; Xu, Haiyan; Tang, Rong (Frontiers in Endocrinology, 2022)
Background: Transferring blastocysts frozen on day 6 (D6) may adversely affect the pregnancy rate compared with day 5 (D5). Moreover, it remains unclear whether delayed embryo transfer affects neonatal birth weight. Methods: A retrospective cohort study consisting of 17,127 singleton births from single frozen embryo transfer (FET) cycles between January 2011 and January 2020 was performed, including 14,166 blastocysts frozen on D5 and 2,961 on D6. The primary outcomes of this study were neonatal birth weight and incidence of small for gestational age (SGA), large for gestational age (LGA), low birth weight (LBW), and macrosomia. Results: The mean neonatal birth weight in the D5 group (3.47±0.49 kg) was significantly higher compared with the D6 group (3.45±0.50 kg), although the discrepancy was only 0.02 kg. Multiple linear regression analysis for birth weight between the two groups showed no statistically significant difference (β= -0.01 t= -1.218; P＞0.05). Logistic regression analysis revealed that the risks of SGA (OR 1.166; 95%CI, 0.911-1.491; P＞0.05), LGA (OR 0.917; 95%CI, 0.831-1.012; P＞0.05), LBW (OR 1.192; 95%CI, 0.926-1.533; P＞0.05), and macrosomia (OR 0.975; 95%CI, 0.864-1.100; P＞0.05) were similar in the two groups after adjusting for confounders. Conclusions: In the FET cycle, the neonatal birth weight and incidence of LGA, SGA, LBW, or macrosomia were similar between the D5 and D6 groups, suggesting that delayed blastocyst transfer would not affect the neonatal birth weight.